Relação tridimensional entre corrupção, compliance e direitos humanos e fundamentais : uma análise sobre os efeitos colaterais dos atos corruptivos com relação a direitos individuais e difusos e à forma como a consolidação da cultura de integridade pode ajudar a garanti-los - Cunha, Matheus Lourenço Rodrigues da (2019)
Corruption is a phenomenon present in the remote humanity’s history. However, it is a complex fact with causes and consequences established in several planes. The conceptualization of the term, the definition of forms as such acts are insurrection in the social sphere, and the integral analysis of the collateral damages caused, not only to the individuals, but also to diffuse and collective rights, were actions neglected over time. However, in reason of advent of capitalism as an economic option, and of globalization with overwhelming consequences for international society, corruption has reached unprecedented levels. As a new and artful form of organized delinquency, with supra-state extent, and endemic, systemic and institutionalized proportions, demanded from the global society and, consequently, from the domestic legal systems, the adoption of rigid norms for its confrontation. However, the fight against corruption, even if it produces results, subjects protected legal interest to injury. Through the Compliance Program, which in its first generation was based on corporate selfregulation to prevent noncompliance with standards, it brought, in addition to preventive prejudice, the hope of postmodern society in the alternative of disseminating values lacking acceptance and practice, such as ethics and integrity, perhaps capable of structuring a new organizational and social culture. Thus, through this possible sociocultural transformation, the renowned corruptive acts could be truly prevented, and the damages to human and fundamental rights derived from them avoided. This is an opportunity. But its real realization, only time will tell.